2011
DOI: 10.1093/humrep/der070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI-assessed body fat content between lean women with polycystic ovary syndrome (PCOS) and matched controls: less visceral fat with PCOS

Abstract: BACKGROUND Polycystic ovary syndrome (PCOS) is a heterogeneous disorder. However, PCOS has a strong resemblance to the metabolic syndrome, including preponderance of visceral fat deposition. The aim of this study is to compare fat distribution between lean women with PCOS and controls matched for body composition but with regular menstrual cycles and proven fertility. METHODS In this prospective cross-sectional study in a fertility outpatient clinic, 10 Caucasian women with PCOS and 10 controls, all with a BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 24 publications
3
32
0
1
Order By: Relevance
“…Considering that the prenatal T-treated female sheep mimic the phenotype of women with PCOS at the reproductive and metabolic level (12) and that these females are kept on a maintenance diet and not allowed to become obese (69), the metabolic phenotype of prenatal T-treated sheep described in this study, namely reduced fat mass lack of insulin resistance, is similar to those reported for the lean-PCOS phenotype (10). Because lean PCOS women are not insulin resistant (42,43), insulin resistance in PCOS women (44 -46) appears to be a trait strongly influenced by obesity (6,65).…”
Section: Translational Relevancesupporting
confidence: 57%
See 2 more Smart Citations
“…Considering that the prenatal T-treated female sheep mimic the phenotype of women with PCOS at the reproductive and metabolic level (12) and that these females are kept on a maintenance diet and not allowed to become obese (69), the metabolic phenotype of prenatal T-treated sheep described in this study, namely reduced fat mass lack of insulin resistance, is similar to those reported for the lean-PCOS phenotype (10). Because lean PCOS women are not insulin resistant (42,43), insulin resistance in PCOS women (44 -46) appears to be a trait strongly influenced by obesity (6,65).…”
Section: Translational Relevancesupporting
confidence: 57%
“…Prenatal T treatment was from day 30 to day 90 gestation for all time points except the 22-month time point, which involved T treatment from day 60 to day 90 of gestation. B, Comparison of directionality of changes in insulin homeostasis (gray boxes) and visceral adiposity (open boxes) after prenatal exposure to T in sheep (our studies) with outcomes from perinatal T/DHT exposure in other species pre-or perinatal T/DHT-treated mice (36), rats (20,(37)(38)(39), cows (40), rhesus monkeys (18,19,41), and women with PCOS (10,(42)(43)(44)(45)(46). Note the differences in age and reproductive status of animals undergoing the tests.…”
Section: Effects Of Prenatal T On Free Fatty Acid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Two MRI studies demonstrated that although increased waist: hip ratio measurements indicated abdominal/visceral fat accumulation, MRI did not show this accumulation (104, 105). Subsequently, one study demonstrated lower visceral fat among lean women with PCOS (353), and another found larger accumulations of visceral fat among both normal-weight and overweight women with PCOS (354). However, these studies used different imaging protocols (ie, single slice vs multislice) and differing PCOS inclusion criteria, which may explain the conflicting results.…”
Section: F Obesity Fat Distribution and Adipose Tissue Function Anmentioning
confidence: 99%
“…In a further study by Huang et al [54] on mainly nonobese women with PCOS vs. control women, MRI did show a significant increase in central (including visceral) fat depots in the PCOS group independent of BMI. In a further study using MRI in a comparison of lean women with PCOS and matched control women, Dolfing et al [55] demonstrated that the PCOS group had less visceral fat than the controls. It is possible that some of the controversy in the current literature regarding BFD in PCOS is related to differences in BMI of the subjects between studies [54].…”
Section: Effects Of Female Obesity On Androgen Levelsmentioning
confidence: 99%